Five years of a comprehensive ST-elevation myocardial infarction protocol and its association with sex disparities. Issue 3 (20th August 2021) - Huded, Chetan P; Kumar, Anirudh; Kassis, Nicholas; Johnson, Michael J; Kravitz, Kathleen; Brown, Abigail; Shanahan, Marguerite; Trentanelli, Karen; Reed, Grant W; Menon, Venu; Krishnaswamy, Amar; Ellis, Stephen G; et al.
Abstract: Aims: To determine whether a comprehensive ST-elevation myocardial infarction (STEMI) protocol is associated with reduced sex disparities over 5 years. Methods and results: This was an observational cohort study of 1833 consecutive STEMI patients treated with percutaneous coronary intervention (PCI) before (1 January 2011–14 July 2014, control group) and after (15 July 2014–15 July 2019, protocol group) implementation of a protocol for early guideline-directed medical therapy (GDMT), rapid door to balloon time (D2BT), and use of trans-radial PCI. In the control group, females had less GDMT (77.1% vs. 68.1%, P = 0.03), similarly low trans-radial PCI (19.0% vs. 17.6%, P = 0.73), and longer D2BT [104 min (79, 133) vs. 112 min (85, 147), P = 0.02] corresponding to higher in-hospital mortality [4.5% vs. 10.3%, odds ratio (OR) 2.44 (1.34–4.46), P = 0.004], major adverse cardiac and cerebrovascular events [MACCE, 9.8% vs. 16.3%, OR 1.79 (1.14–2.84), P = 0.01], and net adverse clinical events [NACE, 16.1% vs. 28.3%, OR 2.06 (1.42–2.99), P < 0.001]. In the protocol group, no significant sex differences were observed in GDMT (87.2% vs. 86.4%, P = 0.81) or D2BT [85 min (64–106) vs. 89 min (65–111), P = 0.06], but trans-radial PCI was used less in females (77.6% vs. 71.2%, P = 0.03). In-hospital mortality [2.5% vs. 4.4%, OR 1.78 (0.91–3.51), P = 0.09] and MACCE [9.0% vs. 11.1%, OR 1.27 (0.83–1.92), P = 0.26] were similar between sexes, but higher NACE in females approached significance [14.8% vs. 19.4%, OR 1.38 (0.99–1.92), P = 0.05] due to higher bleeding risk [7.2% vs. 11.1%, OR 1.60 (1.04–2.46), P = 0.03]. Conclusions: A comprehensive STEMI protocol was associated with sustained reductions for in-hospital ischaemic outcomes over 5 years, but higher bleeding rates in females persisted. Graphical Abstract: